2017
DOI: 10.15294/biosaintifika.v9i1.9191
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Fish Larvae from East Plawangan of Segara Anakan, Cilacap, Central Java, Indonesia

Abstract: Correct identification of fish larvae from East Plawangan is very difficult to be done due to undefined of their morphology, while correct name is an important information for management of that area as spawning and nersery ground. Therefore, so far no scientific report on what species that utilize East Plawangan as their spawning and nursery ground. Cytochrome c oxidase 1 gene provide a precise tool for correct larvae identification. This study aims to test the accuracy of the cytochrome c oxidase 1 gene on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 19 publications
5
27
1
1
Order By: Relevance
“…Similar result was also resulted when the samples were subjected to barcode of life data identification system (BOLD system) where the strains showed the sequence similarity of 98.79%-100% to the sequences of O. guramy available in BOLD system. Nuryanto et al (2017) also found a low intraspecific genetic divergence on fish larvae collected in East Plawangan, Segara Anakan, Cilacap. 0.394 ** 0,551 *** -0,009 ns -Note: * = 0.05 ≥ p ≥ 0.01, ** = 0.01 > p ≥ 0.001, *** = p < 0.001; ns = not significant 14.053 0.455 F ST : 0.508 *** Note: Va and F ST : p-value = 0.000 ± 0.000; * = 0.05 ≥ p ≥ 0.01, ** = 0.01 > p ≥ 0.001, *** = p < 0.001; NS = not significant The result of sequence divergence analysis supported the morphological data, which placed the giant gourami populations from Java and Sumatra into different strains, except for Tambago and Oranye strains.…”
Section: Genetic Divergences Among Strainsmentioning
confidence: 81%
“…Similar result was also resulted when the samples were subjected to barcode of life data identification system (BOLD system) where the strains showed the sequence similarity of 98.79%-100% to the sequences of O. guramy available in BOLD system. Nuryanto et al (2017) also found a low intraspecific genetic divergence on fish larvae collected in East Plawangan, Segara Anakan, Cilacap. 0.394 ** 0,551 *** -0,009 ns -Note: * = 0.05 ≥ p ≥ 0.01, ** = 0.01 > p ≥ 0.001, *** = p < 0.001; ns = not significant 14.053 0.455 F ST : 0.508 *** Note: Va and F ST : p-value = 0.000 ± 0.000; * = 0.05 ≥ p ≥ 0.01, ** = 0.01 > p ≥ 0.001, *** = p < 0.001; NS = not significant The result of sequence divergence analysis supported the morphological data, which placed the giant gourami populations from Java and Sumatra into different strains, except for Tambago and Oranye strains.…”
Section: Genetic Divergences Among Strainsmentioning
confidence: 81%
“…The power of this gene as a species barcode marker because it is changeable enough (Nuryanto et al, 2007;Nuryanto and Kochzius, 2009) due to its high mutation rate which is higher compared to other mitochondrial genome (Hebert et al, 2003). Clear separation of different species and above species category was also reported in fish larvae (Nuryanto et al, 2017), or even among strain within species (Nuryanto et al, 2018).…”
Section: Homology Test and Genetic Species Conceptmentioning
confidence: 94%
“…These observed high values of inter-species genetic divergences are common phenomena. Several studies also reported high genetic divergences among species in various animal groups, such as in fish (Peg et al, 2006;Pereira et al, 2013;Nuryanto et al, 2017;Nuryanto et al, 2018); and Crustacea (Barber et al, 2002).…”
Section: Homology Test and Genetic Species Conceptmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there are many factors affecting the growth of gourami, such as body size and parasite infection. Nuryanto et al (2017) reported that there were genetic variations in the body size of gourami. reported that the prevalence of Trichodina sp.…”
Section: Introductionmentioning
confidence: 99%